HHV-6 Infection in an Immunocompetent Patient with Multi-organ Failure - Wang, Richard N (Cureus, 2019)
Human herpesvirus 6 (HHV-6) is a double-stranded DNA virus part of the Herpesviridae family that colonizes nearly 100% of the human population. The virus is known to be the etiologic agent of roseola infantum, a self-limited disease in childhood and reactivation of the virus later in life is linked to potentially severe manifestations, including encephalitis, in immunosuppressed patients. It is rare in immunocompetent patients, but there have been several reports of encephalitis due to HHV-6 reactivation. We describe here a case of altered mental status and multi-organ failure in an immunocompetent woman, whose cerebrospinal fluid (CSF) was positive for HHV-6 DNA by polymerase chain reaction (PCR).